(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Stilling Basin or water jump pool is a short section of a foamed channel that is constructed as a special structure at the end of overflows or any other source that creates a supercritical flow and the purpose of making it is to form a hydraulic jump inside the pond, in which case the supercritical current, before reaching the non-foamed parts of the river, changes to subcritical current and reduces its extraordinary energy and possible breakdowns is prevented. Any changes in the structure of the relaxation pond directly affect the hydraulic behavior of the flow. The shape and structure of the Stilling Basin and the shape and geometry of the blocks play an important role on the hydraulic performance and fluctuations in flow velocity and jump length in the Stilling Basins. Considering the importance of Stilling Basin blocks and their significant effect on energy dissipation, and considering that various researches have been done on the hydraulic properties of the jump and consequently the characteristics of the Stilling Basins. However, no research has been done on changes in flow velocity and jump length in Stilling Basins with trapezoidal blocks under constant hydraulic conditions. Therefore, in this paper, the length of the hydraulic jump in the Stilling Basin with trapezoidal blocks has been investigated numerically using the Flow-3D model.